Discourse-Level Implicature: A Case for QUD. Issue 3 (3rd April 2017) - Jasinskaja, Katja; Salfner, Fabienne; Freitag, Constantin
Abstract : This article argues that multisentence discourses give rise to Gricean quantity implicatures that go beyond the mere sum of the implicatures of the sentences they consist of. We formulate two theories of discourse-level implicature: the null theory, which only has a mechanism for sentence-level implicature and does not rely on any specific notion of discourse structure, and a theory that assumes that discourse is hierarchically structured by Questions Under Discussion (QUD) and that QUDs can guide the derivation of quantity implicatures at all levels of discourse structure. In two experiments using the inference task paradigm and focusing on sequences of sentences with contrastive topic, the QUD-based theory is shown to make more accurate predictions than the null theory. This finding provides additional motivation for the QUD-based approach to discourse structure.